Design, development and evaluation of a WPE Microworld for learning probability - Su, Ding Kiew. (Faculty of Computer Science and Information Technology, 2006)
Many reforms and innovations efforts especially in computer-supported learning have been continuously undertaken in mathematics education. Microworlds have drawn research attention among the educationists and have the potential in creating a constructivist learning environment. This study developed a mathematical microworld (WPE) to investigate the effectiveness of the microworld learning environment in enhancing the learning of probability and improving the students' attitudes toward mathematics. The topic of probability was chosen because students tend to have difficulty in understanding probability.This research also determined the students' satisfaction with the microworlds' features; the relationship between the students' mathematics achievement using the microworld and the students' characteristics; and the relationship between the students' attitudes toward mathematics after using the microworld and the students' characteristics. This research used a quasi-experimental, non-random pre-and post-test static group research design. Samples consisted of 52 students from two Form Four science classes at two secondary schools in Kuching.Students learned probability using the WPE microworld for 12 to 13 periods.Quantitative and qualitative data collection techniques including questionnaires,interviews and observation were deployed to obtain the required data. Among the research instruments were a pre- and post-test for measuring achievements in probability, questionnaire for attitudes toward mathematics and rubric for evaluating the microworld. Findings of this study showed that the students obtained significantly higher scores in the post-test on probability. The WPE microworld slightly improved students' attitudes toward mathematics. According to the students, WPE as a practical tool helped them to learn and understand probability concepts. Students were satisfied, interested, excited and had fun to explore the microworld while learning the concepts. Generally, they were satisfied with the features of the WPE microworld. Three students who expressed negative reactions on the use of WPE lacked basic computer skills and more comfortable with the traditional rote learning methods. The microworld encouraged interactions among the students and between the students and the instructor. Teachers viewed the WPE microworld as a tool for knowledge construction among the students. Both male and female students learned using technology equally well. However, students with basic computer and Internet skills showed better learning gain, and improved in attitudes toward mathematics after interacting with the WPE microworld. This study also showed the potential of microworlds as a computer-based constructivist learning environment for mathematics learning.